Transport Scheduling with Service-Level Constraints - Complexity and Algorithms - LAU, Hoong Chuin (Institutional Knowledge at Singapore Management University, 2004)
In this paper, we study a problem arising in military transport scheduling. A military organization operates a large fleet of vehicles in a depot to serve the requests of various operational units. Each request has a fixed start and end time, and is served by a prescribed number of vehicles. We address the following two problems : (1) how many vehicles are at least needed to meet a given service level of requests ; and (2) suppose we allow each request to shift its start time by a constant duration, can all the requests be met ?